Optimization of Power System Black Start partition Target Network Taking into Account the Black Start Space-Time Support Capability of New Energy Station - Ruixin WANG; Jiguang SUN; Yan LIU; Lun CHENG; Ting XU; Guanghui SUN (Zhongguo dianli)
Taking into account the spatiotemporal support capacity of new energy station black start, a target network optimization method for power system black-start zoning is proposed to improve unconventional security defense ability of the new power system. Firstly, extended black-start power source (EBSPS) is defined based on the concept of spatiotemporal support capability for black start of new energy stations. Secondly, with the optimization objectives of minimizing electrical distance within the partition and the number of interconnections between partitions, an integer linear programming model for partition target network that takes into account EBSPS is established, in which EBSPS is transformed into a constraint on the number of partitions and other constraints such as power balance, partition connectivity, and flexibility resources are considered as well. Finally, the proposed method was validated through a simulation system to aid in the decision-making process for restoring black start zones in new energy stations.